Is Noncycloplegic Photorefraction Applicable for Screening Refractive Amblyopia Risk Factors? - Zhale Rajavi; Hiva Parsafar; Alireza Ramezani; Mehdi Yaseri (Journal of Ophthalmic & Vision Research, 2012)
Purpose: To compare the accuracy of noncycloplegic photorefraction (NCP) with that of cycloplegic refraction (CR) for detecting refractive amblyopia risk factors (RARFs) and to determine cutoff points. Methods: In this diagnostic test study, right eyes of 185 children (aged 1 to 14 years) first underwent NCP using the PlusoptiX SO4 photoscreener followed by CR. Based on CR results, hyperopia (≥ +3.5 D), myopia (≥ -3 D), astigmatism (≥ 1.5 D), and anisometropia (≥ 1.5 D) were set as diagnostic criteria based on AAPOS guidelines. The difference in the detection of RARFs by the two methods was the main outcome measure. Results: RARFs were present in 57 (30.8%) and 52 (28.1%) of cases by CR and NCP, respectively, with an 89.7% agreement. In contrast to myopia and astigmatism, mean spherical power in hyperopic eyes was significantly different based on the two methods (P < 0.001), being higher with CR (+5.96 ± 2.13 D) as compared to NCP (+2.37 ± 1.36 D). Considering CR as the gold standard, specificities for NCP exceeded 93% and sensitivities were also acceptable (≥ 83%) for myopia and astigmatism. Nevertheless, sensitivity of NCP for detecting hyperopia was only 45.4%. Using a cutoff point of +1.87 D, instead of +3.5 D, for hyperopia, sensitivity of NCP was increased to 81.8% with specificity of 84%. Conclusion: NCP is a relatively accurate method for detecting RARFs in myopia and astigmatism. Using an alternative cutoff point in this study, NCP may be considered an acceptable device for detecting hyperopia as well.